2020
DOI: 10.1038/s41416-020-0751-8
|View full text |Cite
|
Sign up to set email alerts
|

T-type calcium channel inhibition restores sensitivity to MAPK inhibitors in de-differentiated and adaptive melanoma cells

Abstract: BACKGROUND: Drug resistance remains as one of the major challenges in melanoma therapy. It is well known that tumour cells undergo phenotypic switching during melanoma progression, increasing melanoma plasticity and resistance to mitogen-activated protein kinase inhibitors (MAPKi). METHODS: We investigated the melanoma phenotype switching using a partial reprogramming model to de-differentiate murine melanoma cells and target melanoma therapy adaptation against MAPKi. RESULTS: Here, we show that partially repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 47 publications
(74 reference statements)
2
22
0
Order By: Relevance
“…This was directly demonstrated in patient cohorts by in silico genomic analysis of The Cancer Genome Atlas (TCGA) database, which revealed that the upregulation of Cav3.1 or Cav3.2 isoforms were strongly associated to poor outcomes in Kaplan-Meier estimates [16]. Likewise, a TGCA analysis performed by Granados and colleagues demonstrated that melanoma patients with tumors displaying a higher expression of Cav3.2 have a worse survival, although Cav3.1 was neglected from this study [23]. Table 1 summarizes the reported relationships between the expression of TTCCs isoforms, associations with prognosis markers and effects of specific gene silencing.…”
Section: Prognostic Value Of T-type Ca 2+ Channels Expression In Melamentioning
confidence: 64%
See 2 more Smart Citations
“…This was directly demonstrated in patient cohorts by in silico genomic analysis of The Cancer Genome Atlas (TCGA) database, which revealed that the upregulation of Cav3.1 or Cav3.2 isoforms were strongly associated to poor outcomes in Kaplan-Meier estimates [16]. Likewise, a TGCA analysis performed by Granados and colleagues demonstrated that melanoma patients with tumors displaying a higher expression of Cav3.2 have a worse survival, although Cav3.1 was neglected from this study [23]. Table 1 summarizes the reported relationships between the expression of TTCCs isoforms, associations with prognosis markers and effects of specific gene silencing.…”
Section: Prognostic Value Of T-type Ca 2+ Channels Expression In Melamentioning
confidence: 64%
“…However, the analysis of Cav3.2 transcripts in these conditions was not performed. Another recent article reported that TTCC expression was upregulated in partially reprogrammed (by transduction of genes encoding pluripotency factors) BRAF and NRAS mutant-melanoma cells, acquiring features of stemness, slower proliferation and enhanced invasivity [23]. De-differentiated cells increased the expression of transcripts for Cav3.2 (particularly the NRAS mutants), in agreement with its known role in stemness, although the analysis of Cav3.1 transcripts was omitted.…”
Section: T-type Channels As Drivers Of Resistance To Mapk Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been revealed that the treatment of HEK293 cells with 1 µM-1 mM NaHS inhibits voltage-gated T-type specifically Cav3.2 channels by promoting extracellular binding of zinc (Zn 2+ ) [46]. At the downstream, the suppression of T-type channels can result in enhanced antitumor activities and improved sensitivity of cancer cells to drugs [47][48][49]. Studies also show that H 2 S donors can trigger the activation of cellular transporters including ATP-binding cassette transporter A1 (ABCA1) [40] and glutamine transporter-1 (GLT-1) [50] by promoting nuclear translocation of peroxisome-proliferator-activated receptor alpha and inhibiting the extracellular signal-regulated kinase 1/2 (ERK 1/2) respectively.…”
Section: Mechanisms Involved In H 2 S-mediated Cancer Modulationmentioning
confidence: 99%
“…A downregulation of MITF in melanoma cells has been related to an invasive/poorly proliferative phenotype, increased plasticity and acquired therapy resistance to BRAF inhibition [83][84][85]. Induction of phenotype switching towards a more dedifferentiated state drastically enhances the aggressiveness of the tumor, and constitutes an essential mechanism underlying therapy resistance in melanoma patients [2,86,87].…”
Section: Melanoma Plasticitymentioning
confidence: 99%